Thermal denaturation profiles and gel mobility shift analysis of oligodeoxynucleotide triplexes. - Shea, R G (1990)
Oligodeoxypurine- and oligodeoxypyrimidine-containing strands were mixed under conditions conducive to the formation of triple stranded assemblies. The mixtures were characterized both by their UV absorbance change with increasing temperature and by their mobility in non-denaturing polyacrylamide gels. Duplexes 34 bp long containing 15 central purines on one strand and 15 complementary pyrimidines on the other strand yielded new melting transitions and showed different gel mobilities upon combination with oligopyrimidine 15-mers. The dependence of the thermal denaturation profiles on pH, salt concentration, GC content, strand orientation, base mismatches, and strand length was investigated.